Conformación del cepario de hongos aislados de diferentes sustratos en varias regiones de Antioquia, Colombia - Saldarriaga, Yamille; Gutierrez, Ana; Cardona, Nadya; Giraldo, Ines (CATIE, Turrialba (Costa Rica), 2021)
39 referencias bibliográficas